2017
DOI: 10.3390/jof3010009
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Biosynthesis of Novel Multi-Hydroxy Carotenoids in the Red Yeast Xanthophyllomyces dendrorhous

Abstract: The red yeast Xanthophyllomyces dendrorhous is an established platform for the synthesis of carotenoids. It was used for the generation of novel multi oxygenated carotenoid structures. This was achieved by a combinatorial approach starting with the selection of a β-carotene accumulating mutant, stepwise pathway engineering by integration of three microbial genes into the genome and finally the chemical reduction of the resulting 4,4’-diketo-nostoxanthin (2,3,2’,3’-tetrahydroxy-4,4’-diketo-β-carotene) and 4-ket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Rhodotorula rubra), Rhodotorula babjevae, Rhodotorula toruloides Rhodotorula graminis), Sporidiobolus (Sporidiobolus pararoseus, Sporidiobolus johnsonii), and Sporobolomyces (Sporobolomyces uberrimus, Sporobolomyces salmonicolor) have been reported to be prolific producers of torulin and torularhodin [127]. Researchers have discovered pigments such as β-carotene, torulene, and torularhodin from Rhodotorula glutini and multi-hydroxy carotenoids (4,4 -dihydroxy-nostoxanthin and 4-hydroxy-nostoxanthin) from Xanthophyllomyces dendrorhous (Figure 10) [13,128]. (Figure 3b, Figure 9b) [33,36,37,39,41,109].…”
Section: Fungal Species Pigments Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhodotorula rubra), Rhodotorula babjevae, Rhodotorula toruloides Rhodotorula graminis), Sporidiobolus (Sporidiobolus pararoseus, Sporidiobolus johnsonii), and Sporobolomyces (Sporobolomyces uberrimus, Sporobolomyces salmonicolor) have been reported to be prolific producers of torulin and torularhodin [127]. Researchers have discovered pigments such as β-carotene, torulene, and torularhodin from Rhodotorula glutini and multi-hydroxy carotenoids (4,4 -dihydroxy-nostoxanthin and 4-hydroxy-nostoxanthin) from Xanthophyllomyces dendrorhous (Figure 10) [13,128]. (Figure 3b, Figure 9b) [33,36,37,39,41,109].…”
Section: Fungal Species Pigments Referencesmentioning
confidence: 99%
“…Similarly, a study has shown the possible industrial application of the red pigment produced by Paecilomyces sinclairii [126]. (Figure 10) [13,128]. In addition to terrestrial fungi, marine fungi are also very good producers of a variety of unique pigments having promising therapeutic and industrial applications [129,130].…”
Section: Fungal Species Pigments Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidating the functional organization of the multienzyme complex in plants is challenging. Fortunately, reconstruction of the plant carotenoid biosynthetic pathway can be achieved in Escherichia coli or yeast, which both synthesize the isoprenoid precursors (Chen et al, 2010;Pollmann et al, 2017;Ren et al, 2017;Schwartz et al, 2017;Zhang et al, 2018). These heterologous systems are excellent test beds for rapid characterization of carotenoid biosynthetic enzymes of the present and synthetic future, as well as for study of enzyme interactions and biosynthetic complex organization.…”
Section: Solving Structural Mysteries Of the Biosynthetic Machinerymentioning
confidence: 99%
“…Habits of health-conscious people and their concern for the use of chemical additives in food have intensified researches on carotenoid production by biotechnological processes with algae such as Dunaliella salina, Tetraselmis suecica, Isochrysis galbana, Pavlova salina (Ahmed et al, 2014) and Haematococcus pluvialis (Machado Jr. et al, 2016); bacteria such as Rhodopseudomonas palustris (Kuo et al, 2012), Halobacterium salinarum, Halorubrum sodomense, Haloarcula valismortis and Salinibacter ruber (Jehlička et al, 2013); and yeasts such as Phaffia rhodozyma and Xanthophyllomyces dendrorhous (Pollmann et al, 2017;Silva et al, 2016;Cipolatti et al, 2015;Rios et al, 2015), Rhodotorula mucilaginosa (Manimala and Murugesan, 2017;Maldonade et al 2012) and Sporidiobolus pararoseus (Machado and Burkert, 2015;Wei et al, 2014;Manowattana et al, 2018). Carotenoids, such as trans-violaxanthin, antheraxanthin, astaxanthin, lutein epoxide, lutein, zeaxanthin, α-and β-carotene were produced by algae (Ahmed et al, 2014).…”
Section: Introductionmentioning
confidence: 99%